Holocene dust in East Antarctica: Provenance and variability in time and space. (April 2020) - Delmonte, Barbara; Winton, Holly; Baroni, Mélanie; Baccolo, Giovanni; Hansson, Margareta; Andersson, Per; Baroni, Carlo; Salvatore, Maria Cristina; Lanci, Luca; Maggi, Valter
In this paper, we provide a comprehensive overview of the state-of-knowledge of dust flux and variability in time and space in different sectors of East Antarctica during the Holocene. By integrating the literature data with new evidences, we discuss the dust flux and grain-size variability during the current interglacial and its provenance in the innermost part of the East Antarctic plateau as well as in peripheral regions located close to the Transantarctic Mountains. The local importance of aeolian mineral dust aerosol deflated from low-elevation areas of peripheral East Antarctica is also discussed in the light of new data from several coastal, low-elevation sites.